(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2022)
This work is part of the Project called ‘Youth, historical culture, historical awareness and political awareness: quantitative research in schools of the Province of Buenos Aires of the Faculty of Humanities and Education Sciences (Universidad Nacional de La Plata)’. This Project aims to investigate how young people build their historical ideas and recover the decisions made by teachers in history classes to encourage the construction of historical awareness. On this occasion, we analyze interviews conducted with high school history teachers during the 2020 school year, in times of the Covid-19 pandemic. These were carried out in various schools in the district of La Plata, dependent on the Province of Buenos Aires, of state and private management and from the National University of La Plata, whose analysis contributes to the debate on the place of historical awareness in the teaching of History at the secondary level in times of pandemic.